b - d (b, 2006)
Political autobiography of chief minister and a Marxist leader of West Bengal.
In Bengali.
Keywords: Basu, Jyoti, -- 1914-2010.; Politicians -- India -- West Bengal -- Biography; Communists -- India -- West Bengal -- Biography; West Bengal (India) -- Politics and government; West Bengal (India) -- Biography